2017
DOI: 10.1111/asj.12792
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in liver tissue metabolome of lambs fed low‐quality roughage

Abstract: Early experience with low-quality roughage may induce adaptations in ruminants' metabolism. This study was conducted to explore the variation in the hepatic metabolomes of lambs fed low-quality roughage beginning early in life. Five lambs were fed Sudan grass hay (crude protein (CP): 4.6% of the dry matter (DM), neutral detergent fiber, 68.5% of DM) for 6 months during time periods P1, P2 and P3, which consisted of 2 months each. The metabolizable energy (ME) and CP intake satisfied lambs' maintenance requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…[88,112,118] TOF Untargeted biomarker discovery (metabolites). Identification of 499 [112], 286 [88], 60 [92] and 300 [118] [88,92,112,118] Rat urine [225] Human urine [226] Corynebacterium glutamicum [157] Mouse serum/plasma [144,145,150], feces [145], luminal [145], arterial [147] and colonic [144], muscle [139] and brain [143] tissue Sheep liver tissue [230] Pork [231] Renal carcinoma cells [232] CZE(N) HMT sheath liquid [234] TOF Identification of 106 [146], 412 [159] and 367 [161] metabolites Influence of taurine on carbohydrate metabolism [234] Tobacco leaves [159,161] CZE(R) FS 50 mM ammonium acetate…”
Section: Tabulated Summary Of Ce-ms Applicationsmentioning
confidence: 99%
“…[88,112,118] TOF Untargeted biomarker discovery (metabolites). Identification of 499 [112], 286 [88], 60 [92] and 300 [118] [88,92,112,118] Rat urine [225] Human urine [226] Corynebacterium glutamicum [157] Mouse serum/plasma [144,145,150], feces [145], luminal [145], arterial [147] and colonic [144], muscle [139] and brain [143] tissue Sheep liver tissue [230] Pork [231] Renal carcinoma cells [232] CZE(N) HMT sheath liquid [234] TOF Identification of 106 [146], 412 [159] and 367 [161] metabolites Influence of taurine on carbohydrate metabolism [234] Tobacco leaves [159,161] CZE(R) FS 50 mM ammonium acetate…”
Section: Tabulated Summary Of Ce-ms Applicationsmentioning
confidence: 99%
“…To our knowledge, no study has been reported about liver transcriptomics from dairy cows fed different sources of crop byproducts. However, the liver transcriptomics in terms of cows' feed efficiency has been well documented in several studies, [37,39] and the notable consistent results were that lower feed efficiency cows presented upregulated lipid metabolism and inflammation. In ruminants, the lipid metabolism occurs in adipose tissues as well as in liver tissue, with limited metabolic capacity.…”
Section: Discussionmentioning
confidence: 82%